Leadership and the one minute manager increasing effectiveness through situational leadership - Blanchard, Kenneth H.; Zigarmi, Patricia; Zigarmi, Drea (William Morrow, 1985)
Providing a guide to effective business leadership, three management consultants' important concepts and techniques of leadership, including flexibility, diagnosis, contracts, building skill, confidence, and autonomy in others.